Highly efficient catalytic system for liquid-phase oxidation of 1-chloro-n-hexadecane with atmospheric oxygen - V. N. Sapunov; Yu. L. Zotov; Th. T. Nguyen; E. V. Shishkin; Yu. V. Popov (Тонкие химические технологии, 2025)
Objectives. To develop a highly efficient catalytic system for the liquid-phase oxidation of long-chain mono-chlorinated alkanes by oxygen in air to a mixture of high-boiling chlorinated carboxylic acids, which can serve as raw materials for the production of multifunctional additives for polyvinyl chloride.Methods. The liquid-phase oxidation of 1-chloro-n-hexadecane by oxygen in air in the presence of a two-component catalytic system of St2Co(OH) and N-hydroxyphthalimide (N-HPI) was investigated. The air flow rate during the oxidation of 1-chloro-n-hexadecane was controlled by a gas meter. Identification, composition, and content of the starting 1-chloro-n-hexadecane for conversion control were conducted using chromatographic-mass spectrometric analysis on an Agilent GC 7820A/MSD 5975 instrument. The structure of cobalt(III) hydroxystearate was confirmed by infrared spectroscopy.Results. Investigation of a two-component catalytic system St2Co(OH)–N-HPI in the oxidation reaction of 1-chloro-n-hexadecane by oxygen in air revealed that both components of the system participate in the formation of hydroperoxides. This accelerates their formation and contributes to high hydroperoxide content in the reaction mass. It was observed that St2Co(OH) in the two-component catalytic system accelerates the decomposition of hydroperoxides better than St2Co in another two-component catalytic system previously studied, making it promising for application in the process. The oxides thus obtained can serve as raw materials for the production of multifunctional additives for polyvinyl chloride which could lead to improvements in the quality and properties of this material.Conclusions. The investigation into the liquid-phase oxidation of 1-chloro-n-hexadecane by oxygen in air using the two-component catalytic system St2Co(OH)–N-HPI has shown it to be more efficient compared to the two-component catalytic system St2Co–N-HPI. The optimal concentration of the two-component catalytic system St2Co(OH)–N-HPI in the reaction system for the liquid-phase oxidation of 1-chloro-n-hexadecane by oxygen in air has been determined to be 9 mol % of the raw material loading, with a molar ratio of components of 1 : 6. Such a catalytic system enables an acid number in the oxide of 42 mg KOH/g to be attained after 10 h of oxidation.